Is there a role for casein phosphopeptide–amorphous calcium phosphate (cpp-acp) in paediatric dentistry?. (2nd February 2021) - Warner, Claire; Rogers, Helen J
Abstract : In the age of minimally invasive dentistry, products with the ability to prevent and reverse common dental diseases are becoming increasingly popular. Casein phosphopeptide–amorphous calcium phosphate (CPP–ACP) contains the compounds casein, phosphate and calcium, which all have the ability to remineralize enamel. Dental caries, visible demineralization following removal of orthodontic appliances, non-carious tooth surface loss and dentine hypersensitivity due to structural anomalies are frequently seen in children and young people. The evidence for CPP–ACP and fluoride-containing CPP–ACP is positive for managing dental caries and non-carious tooth surface loss, specifically erosion, but is less clear in the management of visible demineralization following orthodontic appliance removal and dentine hypersensitivity owing to structural anomalies. When recommending CPP–ACP-containing products, dental practitioners should be aware of medical and social contra-indications that preclude its use. CPD/Clinical Relevance: CPP–ACP may have a role in the management of common paediatric dental conditions.